IMPROVING EFL STUDENTS' UNDERSTANDING OF ENGLISH DIALECTS BY WATCHING ENGLISH MOVIES OF DIFFERENT DIALECTS WITHOUT SUBTITLES - Cindy Salsabila Ginting; Sahmiral Amri Rajagukguk; Anggun Siska Pratiwi; Sakinah Azzahra (International Journal of Teaching and Learning, 2025)
This study demonstrates that exposing EFL students to English movies of different dialects without subtitles significantly improves their understanding of English dialects. A quasi-experimental design with 10 Indonesian university students was used to evaluate the effectiveness of the method. The treatment group's significant improvement in speaking and listening skills over the control group underscores the value of immersive and naturalistic language learning experiences. These findings suggest that incorporating non-subtitled English movies into EFL curricula can provide students with practical, real-world language exposure that enhances their linguistic and intercultural competence. Therefore, it is recommended that educators incorporate non-subtitled English movies into their teaching strategies to create engaging and authentic learning experiences, improve language comprehension, foster collaborative learning, and increase student motivation.Future research could explore the long-term effects and broader applicability of this method.